Personalized Inclusion with GenAI: An Adaptive Strategy to Support Students with ASD in Higher Education - Otemaier, Rafaela; Quevedo, Eros; Valaski, Joselaine; Tomaschitz, Joice de O. P.; Malucelli, Andreia (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2025)
Inclusion in abstract, cognitively demanding courses is difficult. This study presents an adaptive strategy that merges Universal Design for Learning (UDL) and Generative AI to tailor propositional-logic activities for a student with Autism Spectrum Disorder (ASD). Across four formative, reflective cycles, existing tasks were progressively reshaped; evidence came from observations, journals, and rubrics. The ASD learner showed sustained gains in engagement, conceptual grasp, and autonomy, indicating the value of the approach. The results suggest that educator-mediated GenAI, aligned with UDL, can foster more responsive and inclusive learning in higher education.